2003
DOI: 10.1023/b:phot.0000027518.95032.c1
|View full text |Cite
|
Sign up to set email alerts
|

UV-A Irradiation Guards the Photosynthetic Apparatus Against UV-B-Induced Damage

Abstract: In clusterbean leaves UV-B radiation caused a reduction in contents of chlorophylls and carotenoids and in the efficiency of photosystem 2 photochemistry. The degree of damage was reduced when UV-A accompanied the UV-B radiation. This indicates the counteracting effect of UV-A radiation against UV-B-induced impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In particular, irradiation with ultraviolet (UV) wavelength ranges, consisting of UV-A (400-315 nm), UV-B (315-280 nm) and UV-C (280-100 nm), was effective in inducing the biosynthesis of phytochemicals in plants. 11 St John's wort exposed to UV-B light exhibited an increased hypericin and hyperforin content, 12 and UV-A treatment induced the activation of phenylalanine ammonia lyase (PAL; EC 4.3.1.5), a key enzyme for biosynthesis of secondary metabolites, in tomato seedlings and also induced the accumulation of anthocyanin in fruits and hypocotyls. 13 Moreover, lettuce plants exposed to UV-A or UV-B had an increased concentration of polyphenols, including anthocyanin and flavonoids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, irradiation with ultraviolet (UV) wavelength ranges, consisting of UV-A (400-315 nm), UV-B (315-280 nm) and UV-C (280-100 nm), was effective in inducing the biosynthesis of phytochemicals in plants. 11 St John's wort exposed to UV-B light exhibited an increased hypericin and hyperforin content, 12 and UV-A treatment induced the activation of phenylalanine ammonia lyase (PAL; EC 4.3.1.5), a key enzyme for biosynthesis of secondary metabolites, in tomato seedlings and also induced the accumulation of anthocyanin in fruits and hypocotyls. 13 Moreover, lettuce plants exposed to UV-A or UV-B had an increased concentration of polyphenols, including anthocyanin and flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have shown the accumulation of phytochemicals in plants with changes in lighting conditions. In particular, irradiation with ultraviolet (UV) wavelength ranges, consisting of UV‐A (400–315 nm), UV‐B (315–280 nm) and UV‐C (280–100 nm), was effective in inducing the biosynthesis of phytochemicals in plants . St John's wort exposed to UV‐B light exhibited an increased hypericin and hyperforin content, and UV‐A treatment induced the activation of phenylalanine ammonia lyase (PAL; EC 4.3.1.5), a key enzyme for biosynthesis of secondary metabolites, in tomato seedlings and also induced the accumulation of anthocyanin in fruits and hypocotyls .…”
Section: Introductionmentioning
confidence: 99%
“…Light quality, in particular, had a major impact on phytochemicals: carotenoids (b-carotene, lutein), phenolics (anthocyanins, flavonoids), and vitamin C respond differently to LED quality in terms of ultraviolet-A (315-380 nm), blue (425-490 nm), green (490-550 nm), red (625-700 nm), and far red (700-740 nm) radiation in green vegetables, tomato, cucumber, and sweet pepper (Olle and Vir sil_ e, 2013). Ultraviolet, which has high energy and short wavelength, is known to promote biosynthesis of phytochemicals by inducing plants' defense mechanisms as this radiation usually stresses the plant (Gartia et al, 2003). Among the visible spectrums, red and blue light are important for photosynthesis and have often been used in plant research and commercial production.…”
mentioning
confidence: 99%
“…However, only a few researches were conducted on plant responses to UV-A band (White andJahnke 2002, Close et al 2007). UV-A radiation may have little biological effectiveness according to the commonly used biological spectra weighting functions (BSWF) (Green et al 1974), but some indoor and field studies suggest that UV-A alone inhibits plant growth and development, e.g. hypocotyl elongation (Ballaré et al 1991), leaf expansion (Häder 1996), inflorescence emerging and flower opening (Day et al 1999).…”
mentioning
confidence: 99%
“…hypocotyl elongation (Ballaré et al 1991), leaf expansion (Häder 1996), inflorescence emerging and flower opening (Day et al 1999). The positive effects of UV-A were also observed in protection of the photosynthetic apparatus against UV-B-induced damage by restoring photosystem 2 (PS2) activity and facilitating energy dissipation through xanthophyll cycle (Gartia et al 2003), and were widely evidenced in photo-repair processes for DNA damage (Takeuchi et al 1996).…”
mentioning
confidence: 99%